Rxrs and their partner receptor genes inducing masculinization plausibly mediated by endocrine disruption in Paralichthys olivaceus. Issue 226 (February 2023) - Zou, Congcong; Wang, Lijuan; Shu, Chang; Tan, Xungang; Wu, Zhihao; Zou, Yuxia; Li, Ze; Wang, Guoyu; Song, Zongcheng; You, Feng
Abstract: Retinoid X receptors (RXRs) can form homo- or heterodimers with orphan receptors involved in multiple intertwined signaling pathways. However, there is limited study on the formation of sex phenotypes and the regulation of steroidogenesis by RXRs in fish. Here, in Paralichthys olivaceus, we first indicated that PPARγ::RXRα was predictably a transcription factor for steroidogenesis genes, and Foxl2 and Dmrt1 were also transcription factors for rxr s and their partner receptor genes. When the flounder fry were exposed to LG100268 (LG, RXRs agonist, 50 mg/kg diet), the percentage of males increased from 50% to 71.4%. Before histological differentiation of the flounder ovary (3 cm TL) and testis (6 cm TL), the transcripts of rar β and rar γ (P < 0.05) were activated, and the steroidogenesis gene Hsd3b1 was down-regulated (P < 0.05). The ratios of testosterone (T)/17β-estradiol (E2) were all greatly increased (P < 0.05), and the ratio of 11-ketotestosterone (11-KT)/E2 was elevated at 3 cm TL. Moreover, LG was used to treat the cultured gonads in vitro (10 μM) and the fish with intraperitoneal injection in vivo (12 mg/kg body weight), respectively. LG was able to up-regulate rxr γ, rar γ, and ppar δ, and Hsd3b1 was significantly up-regulated (P < 0.05). The ratios of 11-KT/E2 in the culture medium and in the ovaries of the fish were decreased. Furthermore, the recombinant flounder Foxl2 protein was able to significantly down-regulate ppar γ (P < 0.05 ) and tr β (P < 0.01) in the ovaries in vitro, and the result of the Dmrt1 in the testes was opposite to that of the Foxl2, probably indicating a feedback loop between RXRs' partner receptors and Foxl2/Dmrt1. These findings introduce for the first time the mode of action of RXRs on the flounder steroidogenesis and provide important data to learn the potential function of RXRs in fish sex differentiation and the potential role of RXRs in aquatic animals in the presence of water pollutants. Highlights: The RXRs agonist LG100268 could induce masculinization of the flounder juvenile. LG could affect the expression pattern of rxr s and their partner receptor genes. LG could alter the expression of the genes related to steroidogenesis. During the gonadal differentiation, LG significantly increased the ratio of T/E2. There might be a feedback loop between the partner receptors of RXRs and Foxl2/Dmrt1.